Food-Aid Quality Correlates Positively With Diet Quality of Food Pantry Users in the Leket Israel Food Bank Collaborative - Efrati Philip, Dana; Baransi, Ghada; Shahar, Danit R.; Troen, Aron M. (Frontiers in Nutrition, 2018)
Introduction: In many affluent countries, including Israel, networks of food banks and pantries have increasing responsibility to alleviate endemic poverty and food insecurity. While they may relieve acute hunger, their long-term influence on health and well-being is poorly understood. Methods: An exploratory cross-sectional telephone survey assessed both adequacy and quality of food aid provided via food pantries in the Leket Israel food bank network, in relation to recipients’ dietary needs and health. The quality of food baskets and recipient diets were given a Healthy Portions Score (HPS) to measure compliance with Government guidelines for a “Basic Healthy Food Basket”, and a Nutrient Density Score (NDS) to capture how well the food achieved the recommended dietary allowance (RDA) for vital macro and micronutrients. A total of 105 pantry users were surveyed from 16 pantries around the country. Results: The basket HPS correlated positively and highly significantly with dietary quality (individual NDS) after adjusting for gender, marital status and country of birth (standardized β= 0.22, p=0.03). Nearly half (46%) reported food insecurity with hunger. Two thirds were overweight or obese, and anemia, cardiovascular and metabolic disease were prevalent. The average food basket provides 30% of energy, 55% of protein, 50% of fiber, but only 33% or less of the household requirement for most minerals and vitamins. Only 60% of participants met their estimated energy requirements, and the intake of many essential micronutrients was well below the RDA. Fruits and vegetable portions contributed by Leket Israel correlated positively with the dietary quality (individual NDS) after adjustment for the same covariates (Standardized β= 0.20, p=0.04). Discussion: A structured telephone survey proved a feasible method to study the impact of food-aid quality on the nutrition and health of food pantry users in an affluent country. Food baskets with fruits, vegetables and higher quality nutrition were correlated with healthier diets among the recipients. Data correlating food-aid quality and recipient diet and health is essential to effective policy making.